The focus of spatial attention during the induction of central sensitization can modulate the subsequent development of secondary hyperalgesia. (March 2020) - Filbrich, Lieve; van den Broeke, Emanuel N.; Legrain, Valéry; Mouraux, André
Abstract: Intense or sustained activation of peripheral nociceptors can induce central sensitization. This enhanced responsiveness to nociceptive input of the central nervous system primarily manifests as an increased sensitivity to painful mechanical pinprick stimuli extending beyond the site of injury (secondary mechanical hyperalgesia) and is thought to be a key mechanism in the development of chronic pain, such as persistent post-operative pain. It is increasingly recognized that emotional and cognitive factors can strongly influence the pain experience. Furthermore, through their potential effects on pain modulation circuits including descending pathways to the spinal cord, it has been hypothesized that these emotional and cognitive factors could constitute risk factors for the susceptibility to develop chronic pain. Here, we tested whether, in healthy volunteers, the experimental induction of central sensitization by peripheral nociceptive input can be modulated by selective spatial attention. While participants performed a somatosensory detection task that required focusing attention towards one of the forearms, secondary hyperalgesia was induced at both forearms using bilateral and simultaneous high-frequency electrical stimulation (HFS) of the skin. HFS induced an increased sensitivity to mechanical pinprick stimuli at both forearms, directly (T1) and 20 min (T2) after HFS, confirming the successful induction of secondary hyperalgesia at both forearms. Most importantly, at T2, the HFS-induced increase in pinprick sensitivity as well as the area of secondary hyperalgesia was greater at the attended arm as compared to the non-attended arm. This indicates that top-down attentional factors can modulate the development of central sensitization by peripheral nociceptive input, and that the focus of spatial attention, besides its modulatory effects on perception, can affect activity-dependent neuroplasticity.